2016
DOI: 10.1073/pnas.1523906113
|View full text |Cite
|
Sign up to set email alerts
|

Strain-enhanced stress relaxation impacts nonlinear elasticity in collagen gels

Abstract: The extracellular matrix (ECM) is a complex assembly of structural proteins that provides physical support and biochemical signaling to cells in tissues. The mechanical properties of the ECM have been found to play a key role in regulating cell behaviors such as differentiation and malignancy. Gels formed from ECM protein biopolymers such as collagen or fibrin are commonly used for 3D cell culture models of tissue. One of the most striking features of these gels is that they exhibit nonlinear elasticity, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
222
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(236 citation statements)
references
References 51 publications
13
222
1
Order By: Relevance
“…Furthermore, as fibroblasts move, they contract and align ECM fibers depending on their direction of motion (18,19). Recent experimental results also show that a fiber network under strain over a threshold time can change its structural and A B properties in a nonreversible fashion (21). As a result, the fiber network at some point in space can "remember" the average orientation of the particles that have previously traversed close to that location (22).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as fibroblasts move, they contract and align ECM fibers depending on their direction of motion (18,19). Recent experimental results also show that a fiber network under strain over a threshold time can change its structural and A B properties in a nonreversible fashion (21). As a result, the fiber network at some point in space can "remember" the average orientation of the particles that have previously traversed close to that location (22).…”
Section: Resultsmentioning
confidence: 99%
“…We must point out that local fiber recruitment is closely related to the inelastic (history-dependent) bulk response of biopolymer networks (27)(28)(29). In particular, mechanical straining accelerates the dissociation of weak cross-links (30), leading to macroscale plastic deformation of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mechanical straining accelerates the dissociation of weak cross-links (30), leading to macroscale plastic deformation of the matrix. It had been shown that such an effect is more prominent at long timescales (27) and large strains (28,29), whereas it diminishes with the addition of permanent covalent cross-links (28,29). In contrast, networks that only have weak crosslinks are more dissipative and undergo larger stress relaxations (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress relaxation tests and creep tests were conducted using an AR-G2 stress-controlled rheometer (TA Instruments, DE). Samples were prepared for rheological analysis following a previously published method 51 . Alginate solution was directly deposited between two plates of the rheometer immediately after crosslinking, but before gelation.…”
Section: Methodsmentioning
confidence: 99%